2019
DOI: 10.3390/s19132999
|View full text |Cite
|
Sign up to set email alerts
|

Combining Inter-Subject Modeling with a Subject-Based Data Transformation to Improve Affect Recognition from EEG Signals

Abstract: Existing correlations between features extracted from Electroencephalography (EEG) signals and emotional aspects have motivated the development of a diversity of EEG-based affect detection methods. Both intra-subject and inter-subject approaches have been used in this context. Intra-subject approaches generally suffer from the small sample problem, and require the collection of exhaustive data for each new user before the detection system is usable. On the contrary, inter-subject models do not account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…Nevertheless, an interesting question to be asked is at what depth of the neural network does stratified normalization help increase the accuracy. To answer this question, we further analyzed the emotion recognition accuracy of the models, and their ability to capture and exploit the brain signature of each participant – defined as the part of information extracted from the brain signals that is specific to that participant (also called subject-related component by Arevalillo-Herráez et al (2019)), such that it can directly inform us on which participant it’s been extracted from . Intuitively, we would expect the emotion recognition accuracy to increase with each layer of the neural network, while the brain signature would fade out due to a decrease of the inter-participant variability with each data normalization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an interesting question to be asked is at what depth of the neural network does stratified normalization help increase the accuracy. To answer this question, we further analyzed the emotion recognition accuracy of the models, and their ability to capture and exploit the brain signature of each participant – defined as the part of information extracted from the brain signals that is specific to that participant (also called subject-related component by Arevalillo-Herráez et al (2019)), such that it can directly inform us on which participant it’s been extracted from . Intuitively, we would expect the emotion recognition accuracy to increase with each layer of the neural network, while the brain signature would fade out due to a decrease of the inter-participant variability with each data normalization.…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Koelstra et al (2012) and Jatupaiboon et al (2013) already gave the first insights into the advantages of this approach after applying participant-based data normalization to reduce the inter-participant variability. Later on, the work of Arevalillo-Herráez et al (2019) exploited this result and proposed a nonlinear data transformation that seamlessly integrated individual traits into an inter-participant approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of four classes of emotions (HVHA, HVLA, LVHA, and LVLA) the reported recognition rates decrease to a much larger extent [17]. Fourth, due to the highly subjective and dynamic nature of emotion, few pieces of research have proposed subject-dependent approaches with better recognition performance; however, subject-dependent approaches besides higher recognition rates require large training data from each subject and are not capable of being applied to unseen subjects [46]. Therefore, studies reported for subject-independent approaches [47,48] are more reliable for emotion elicitation tasks from a broader perspective as compared to the results obtained using subject-dependent approaches [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The second category with specialized pre-processing consists of steps required specific to the emotion elicitation algorithm. These steps include baseline removal and Z-score normalization, inspired by its significance in many studies such as [46,[58][59][60][61].…”
Section: Pre-processingmentioning
confidence: 99%
“…Another early research approach is to build individual models adapted to each user, known as subject-dependent (intra-subject) models. The benefits of the subject-dependent models have recently been proved in several cases such as Electroencephalography (EEG) signals in [20][21][22] or keyboard and mouse signals in [23]. This approach offers better detection accuracy, by offering models adapted to each subject.…”
Section: Introductionmentioning
confidence: 99%